Effective strategies for teaching academic writing and literary reading: Perceptions and challenges of STEM students in Chinese higher education - Cheung Ching Ching, Karen; Mao, Peijie (American Journal of STEM Education, 2025)
Drawing on the experiences and practices of teaching "Literature and Writing" courses at ShanghaiTech University, this paper explores effective ways to integrate academic writing and literary reading in college literature classes to develop students ’ high cognitive abilities through a writing-to-learn approach. The study examines STEM students ’perceptions of this approach to teaching academic writing and literary reading. Data was collected through a survey instrument and analyzed using descriptive statistics. The results reveal the reading and writing habits of college students in STEM majors and their perspectives on one-on-one writing conferences. This paper discusses common writing challenges faced by college students and proposes possible solutions for teachers to help students cultivate academic writing and critical thinking skills through a blend of WTL and interdisciplinary teaching approach.